Extracorporeal membrane oxygenation as a bridge to durable mechanical circulatory support or heart transplantation. Issue 7 (July 2022) - Hansen, Breanna; Singer Englar, Tahli; Cole, Robert; Catarino, Pedro; Chang, David; Czer, Lawrence; Emerson, Dominic; Geft, Dael; Kobashigawa, Jon; Megna, Dominick; Ramzy, Danny; Moriguchi, Jaime; et al.
Background: Patients with cardiogenic shock may require extracorporeal membrane oxygenation (ECMO) prior to durable mechanical circulatory support (dMCS) or heart transplantation (HTx). Methods: We investigated the clinical characteristics and outcomes of adult patients with ECMO support as bridge to dMCS or HTx between 1/1/13 and 12/31/20. Results: Of 57 patients who underwent bridging ECMO, 41 (72%) received dMCS (approximately half with biventricular support) and 16 (28%) underwent HTx, 13 (81%) after the 2018 UNOS allocation system change. ECMO → HTx patients had shorter ventilatory time (3.5 vs 7.5 days; p = 0.018), ICU stay (6 vs 18 days; p = 0.001), and less need for inpatient rehabilitation (18.8% vs 57.5%; p = 0.016). The 1-year survival post HTx was 81.3% in the ECMO → HTx group and 86.4% in the ECMO → dMCS group ( p = 0.11). For those patients in the ECMO → dMCS group who did not undergo HTx, 1-year survival was significantly lower, 31.6% ( p = 0.001). Conclusion: Patients on ECMO who undergo HTx, with or without dMCS bridge, have acceptable post-HTx survival. These findings suggest that HTx from ECMO is a viable option for carefully selected patients deemed acceptable to proceed with definitive advanced therapies, especially in the era of the new UNOS allocation system. Graphical Abstract